Diversity of information needs within the UP LGBT student community - Chan, Mikee Jay Camille M. (2017)
This study explored the information needs of LGBT undergraduate students of UP Diliman. It aimed to assess the similarities and differences of information needs of each class, of the LGBT community, in relation to their sexual and gender identities. Guided by Robert Taylor's question formation, the researcher disseminated online survey on various social media and conducted a series of focus group discussions to each member of LGBT to gain deeper insight about the information they seek. It was discovered in the study that the information needs of each member of LGBT undergraduate students of UP Diliman are similar to each other. All of them still seek coming out information, mental health information, and support groups. There is a slight difference discovered in their information needs. But it is due to some factors such as availability of resources. The study concluded that the information needs of the UP Diliman LGBT students are affected by their academic needs, since most of them came out or had realized that they are nonbinary after attending gender and sexuality courses in UP Diliman.